Theories of acids and especially the basicity of acids - Perkins, Edith (My University, 1900)
Introduction: The ancients possessed very little knowledge of the acids—acetic acid in the form of vinegar being, in fact, the only one know to them, and its solvent power was greatly overrated. Among the Arabists, acids were better and more widely known. Basil Valentine speaks of the preparation of nitric acid from saltpeter and sulfuric acid as a very old process. He himself obtained sulfuric acid by heating green vitriol and pebbles; and in this same way, he made “spiritus salus” (hydrochloric acid) by heating green vitriol and common salt. Aqua regia was known to both Gerber and Valentine. Oil of Vitriol was highly valued, being regarded as the “Sulphur philosophorum”, and it was thought, might lead to the discovery of the “materia prima”. From the time of Lavoisier, Chemistry took its place among the sciences, and to the “Father of Chemistry” we owe much of our present knowledge. Lavoisier and Berzelius believed that the properties of acids depended upon their containing oxygen, and that oxygen was, therefore, an unfailing constituent of all acids. When Cavendish discovered that water was formed upon burning hydrogen, Lavoisier at once saw the way to the fulfilment of his oxygen theory. He claimed that the hydrogen came from the water; that the oxygen was fixed in the metal; and hence it was the metallic oxide, not the metal that was dissolved by the acid. He says—“The combustible body, is, as a rule, converted into an acid by its combination with pure air, but the metals, on the contrary, into metallic calces.” For him, sulfuric, phosphoric, and nitric acids, consisted of Sulphur, phosphorous, saltpeter gas (NO) and oxygen. For him, too hydrochloric acid consisted of oxygen combined with the radical “muriatique”; the chlorine liberated by its oxidation was regarded as oxidized hydrochloric acid.
Citation: Perkins, Edith. Theories of acids and especially the basicity of acids. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Chemistry; Acids; Theses